Sentidos De Matoneo Escolar En Los Estudiantes Del Programa De Licenciatura En Educación Física De La Universidad Del Quindío (2014)
This research makes an understanding to the global phenomenon of school bullying through the senses that the undergraduate students in physical education and sports have as it is evidenced in research done in Colombia and around the world and it is present in classes at the higher education level. Therefore, this study was aimed at uncovering the meanings that the students of physical education and sports have pretends to have more tools that lead to improve the processes of educational training provided to students in this program. The methodological structure that was implemented was the comprehensive approach using the descriptive-reflexive ethnography research where the author observed the signs of school bullying that were presented in two groups. One of the groups was found contaminated. On the other hand, the researcher visualized and identified the actors in an alleged case of school bullying through a field journal using direct observation to describe the signs of bullying presented and subsequently the interview which was used later in a triangulation process allowing to reveal the senses that these students had about this phenomenon.